Educational levels and the functional dependence of ischemic stroke survivors Nível de escolaridade e dependência funcional em sobreviventes de acidente vascular cerebral isquêmico - Tiótrefis G. Fernandes; Alessandra C. Goulart; Waldyr R. Santos-Junior; Airlane P. Alencar; Isabela M. Benseñor; Paulo A. Lotufo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2012)
We evaluated the functional dependence of stroke survivors from the Study of Stroke Mortality and Morbidity, using the Rankin Scale. Out of 355 ischemic stroke survivors (with a mean age of 67.9 years), 40% had some functional dependence at 28 days and 34.4% had some functional dependence at 6 months. Most predictors of physical dependence were identified at 28 days. These predictors were: low levels of education [illiterate vs. > 8 years of education, multivariate odds ratio (OR) = 3.7; 95% confidence interval (95%CI): 1.60-8.54] and anatomical stroke location (total anterior circulation infarct, OR = 16.9; 95%CI: 2.93-97.49). Low levels of education and ischemic brain injury influenced functional dependence in these stroke survivors. Our findings reinforce the necessity of developing strategies for the rehabilitation of stroke patients, more especially in formulating specific strategies for care and treatment of stroke survivors with low socioeconomic status. Foi avaliada a dependência funcional em sobreviventes de acidente vascular cerebral (AVC) do Estudo da Mortalidade e Morbidade do Acidente Vascular Cerebral, utilizando a Escala de Rankin. De 355 sobreviventes com AVC isquêmico (idade média de 67,9 anos), 40% tinham dependência funcional em 28 dias e 34,4% em 6 meses. Os principais indicadores de dependência física foram identificados em 28 dias, e eram: baixa escolaridade (analfabetos vs. > 8 anos de educação, RC = 3,7; IC95%: 1,60-8,54) e localização do AVC (infarto circulação total anterior, RC = 16,9; IC95%: 2,93-97,49). Baixo nível educacional e insulto cerebral isquêmico influenciaram o grau de dependência funcional nesses sobreviventes de AVC. Nossos achados reforçam a necessidade de desenvolvimento de estratégias para reabilitação de pacientes com AVC e formulação de estratégias específicas de atenção e tratamento para essas pessoas, especialmente na população com baixo nível socioeconômico.